Investigation of Intermetallic Phase Formation and Structural Analysis in Annealed Al/Cu Bilayer Thin Films. - Mohd Rosli, ZULKIFLI; halim, z; azizi, mat yajid; ali, R (2014)
The growth of intermetallic phases in Al/Cu bilayers thin film having 2/3 layer thickness ratios were characterized by X-ray powder diffraction (XRD), energy dispersive X-ray (EDX) and transmission electron microscopy (TEM). In annealing temperature of 200 oC, the growth is controlled by Cu diffusion which resulted to formation of θ- Al2Cu, η- AlCu, ζ- Al3Cu4 and γ-Al4Cu9 phase.